STUDY OF INDIGENOUS/TRADITIONAL MEDICINAL PLANT KNOWLEDGE- AN ENDEAVOUR TOWARDS NEW DRUG DISCOVERY - Lone, Parvaiz; Bhardwaj, Ajay; Bahar, Fayaz (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The documentation and phytochemical screening of medicinal plants has been an important way over the years for the discovery of new drugs and pharmaceutical products. Bandipora, one of the northern districts of Kashmir, India, is rich in ethnic and biological diversity. Owing to increasing demand and subsequent pressure on medicinal plants, it is highly imperative to document their traditional uses, understand their distribution and diversity, and highlight their availability in their natural habitats. To this end, the present study was carried out to elicit a firsthand wealth of information on the traditional medicinal uses of plants practiced by the local populace of this remote district.Material and Methods: Frequent field trips and plant collections were made between March 2011 to October 2012 and the methods used to gather ethnomedicinal data included semi-structured interviews, focus group discussions and walk-in-the-woods with local knowledgeable elders, traditional practitioners (Bhoeris) and tribals (Gujjars and Bakkerwals). The collected data was analyzed with three quantitative tools viz. the informant consensus factor (Fic), fidelity level (FL) and use value (UV). Results: A total of 131 plant species belonging to 120 genera and 59 different families were found to be used as remedies for curing various human and livestock ailments. Out of 131 species, angiosperms comprised the highest number (124 species) followed by pteridophytes (4 species) and gymnosperms (3 species). Two dominant families were Asteraceae (16 species) and Lamiaceae (9 species). The highest informant’s consensus factor (Fic) value was 0.95 for insect stings, followed by dermatological, hair ailments, anticancer/tumor (0.90 each), which indicated best agreement among informant knowledge on medicinal plant used to treat ailments in these categories while the lowest Fic value of liver disorders and fever (0.63 each) indicated less agreement among informant knowledge on medicinal plant used to treat ailments in these categories. The 100% FL was expressed by 6 plant species for dermatological disorders followed by 3, 1, 1, 1 and 1 for mouth ailments, cardiovascular, joint ailments, gastrointestinal and insect stings category respectively. Use value was high for Artemisia absinthium (0.70), Cannabis sativa and Saussurea costus (0.47 each), Calendula officinalis (0.45) and Taraxacum officinale (0.39). The lowest use value was calculated for Ranunculus arvensis (0.01), with only three people reported the utility. Conclusion: Since drug discovery from medicinal plants continues to provide new and important leads against various pharmacological targets, an effort to collect medicinal plants and their associated traditional knowledge could serve an important tool for the discovery new potent compounds because if the documented plants are subjected to thorough phytochemical and pharmacological investigations, new potent leads against various pharmacological targets could definitely be discovered as there is no doubt that botanic gems are still found in the world.